Evaluation of the anti-proliferative and antimicrobial activities of three types of trigona spp. honey - Zaib, Nik Amalia Nasratiena Mat (2018)
Trigona spp. known as Kelulut in Malaysia, was a small stingless bee from tribe Meliponini. This stingless bee produced honey which was used in wound healing, increase immune system, killing bacteria, treatment of bronchial phlegm, relieving sore throat, cough, and cold. In this study, the Trigona spp. honeys were tested to determine the anti-proliferative activity against MCF-7 breast cancer cell lines, HeLa cervical cancer cell and SVG normal glial cell using MTT assay. The antimicrobial activities of Trigona spp. honey were tested by determination of minimum inhibitory concentration (MIC) against E. coli, S. aureus and C. albicans using microdilution method. Then minimum bactericidal concentration (MBC) or minimum fungicidal concentration (MFC) value were determined by sub culturing the contents of nutrient broth used for MIC tests on nutrient agar using sterile wire loop and making a strike on the media to see bacteria growth after incubating at 37 °C for 24 hours. Absence of growth of E. coli and S. aureus were indicated the MBCs of the honeys while MFC were determined by absence growth of C. albicans. Lastly, the time kill assay were determined at concentrations of 0.5 x MIC, 1 x MIC and 2 x MIC and were incubated for varied time intervals (0, 2, 4, 24 hours). The number of living cells (CFU/mL) of each sample was determined using the agar plate count method. As the result, both H. itama honey and T. laeviceps honey were showed inhibition in the growth ofMCF-7 breast cancer cell line and HeLa cervical cancer cell lines. However, the T. laeviceps honey has better anti-proliferative activity on MCF-7 cell lines but weak anti-proliferative activity on HeLa cell line. In contrast, H. itama honey showed better anti-proliferative activity on HeLa cell line but much weaker on MCF-7 cell lines. Besides, Trigona spp. honeys were non-toxic to the normal cell line while toxic to the cancer cell line. The undiluted H. itama honey (100 % concentration) promoted normal cell proliferation. For antimicrobial activity, MIC values of the Trigona spp. honey against E. coli were ranged 3.125 % to 6.25 % while against S. aureus were ranged 3.125 % to 12.5 %. Besides, C. albicans showed low susceptibility to all types of honeys. Time kill assay showed that have bactericidal activity against E.coli and S. aureus. The stingless bee honey showed the reduction of E.coli after 24 hours while the reduction of S. aureus was showed after 2 hours of treatment. The anti-proliferative and antimicrobial activities of the honey were correlated with their total phenols content, hydrogen peroxide activity, acidity and hyper-osmolarity of the honey. We concluded that the Trigona spp. honey showed varied inhibitory effects on different cancer cell lines and broader-spectrum antibacterial activity but weak in antifungal activity. However, further investigation of Trigona spp. honey mechanisms of action, in vivo studies, and toxicological effects will be necessary to establish their safety as anticancer and antimicrobial agents.